HUBUNGAN PENINGKATAN KADAR MALONDIALDEHIDA PLASMA DENGAN VOLUME INFARK CT SCAN KEPALA PADA STROKE ISKEMIK AKUT - Retnaningsih, Giri Wicaksono, Widiastuti (Neurona Majalah Kedokteran Neuro Sains, 2013)
INTRODUCTION STROKE IS A NEUROVASCULAR DISORDER THE THIRD LEADING CAUSE OF DEATH ON THE WORLD MAJORITY OF STROKE ARE ACUTE ISCHEMIC STROKE 7080 WHICHHAD INFARCT EXPANSION IN 4872 HOURS BRAIN ISCHEMIA INDUCES THE RELEASE OFFREE RADICALS THAT REACTS WITH POLYUNSATURATED FATTY ACIDS PUFA THROUGHOUT THE LIPID PEROXIDATION IN CONSEQUENCE OF MALONDIALDEHYDE MDA GENERATION